Monitoring water quality parameters for Case II waters in Cyprus using satellite data - Papoutsa, Christiana; Retalis, Adrianos; Toulios, Leonidas G.; Hadjimitsis, Diofantos G. (My University, 2014)
Remote sensing technology has been widely used for monitoring water quality parameters such as suspended solids (turbidity), Secchi Disk, chlorophyll, and phosphorus. Suspended matter plays an important role in water quality management of several inland- (such as lakes and reservoirs) and coastal-water bodies and can be used to estimate the Trophic State Index of different water bodies. However synoptic information on water quality parameters at a systematic basis is difficult to be obtained from routine in situ monitoring programs since suspended matter, phosphorus, and chlorophyll are spatially inhomogeneous parameters. To meet this need, an integrated use of Landsat satellite images, in situ data and water quality models can be used. Several algorithms were developed at a previous stage using water quality data collected during the in situ sampling campaigns taken place in 2010 and 2011 over Asprokremmos Reservoir (Paphos District) for the assessment of turbidity, Secchi Disk, and Trophic State Index fluctuations using spectroradiometric data. Remotely sensed data were atmospherically corrected and water quality models for the estimation of both the turbidity- and Secchi Disk- concentrations were further calibrated using in situ data for the case of Asprokremmos Reservoir and several coastal over Cyprus coastline (Limassol and Paphos District Areas). This methodology can be used as a supporting monitoring tool for water management authorities "gaining"? additional information regarding the spatial and temporal alterations of the turbidity- and Secchi Disk- concentrations and the Trophic State Index values over several Case II water bodies.
Keywords: Case II Waters; Cyprus; Landsat; Secchi Disk; Trophic State Index; Turbidity